2015
DOI: 10.1177/0098628315603060
|View full text |Cite
|
Sign up to set email alerts
|

Incentivizing Multiple Revisions Improves Student Writing Without Increasing Instructor Workload

Abstract: Previous research has shown that when students are required to submit a draft and a revision of their writing, large proportions of students do not improve across drafts. We implemented a writing assignment in which students were permitted to submit up to four optional drafts. To encourage substantive revisions, students were awarded additional points if they received all points on the grading rubric. Based on the grades of the instructors, 31% of students eventually earned perfect scores in this assignment, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Thus, the seemingly greater lessons learned from electronic feedback on a different, earlier assignment did not transfer to subsequent writing. This lends further support to the suggestion by Stellmack, Sandidge, Sippl, and Miller (2015) that the process of revising writing after review should be viewed as a process whereby an author responds to and attempts to satisfy particular reviewers rather than a process in which writing ability itself is improved to any great extent.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, the seemingly greater lessons learned from electronic feedback on a different, earlier assignment did not transfer to subsequent writing. This lends further support to the suggestion by Stellmack, Sandidge, Sippl, and Miller (2015) that the process of revising writing after review should be viewed as a process whereby an author responds to and attempts to satisfy particular reviewers rather than a process in which writing ability itself is improved to any great extent.…”
Section: Discussionsupporting
confidence: 66%
“…It is also possible that instructors of courses across our curriculum did not focus their teaching or feedback on the specific writing skills assessed by the rubric we used, or that they did not provide sufficient opportunities for revisions that would enable students to practice and refine those skills. Research indicates that students’ writing can be improved through feedback and revision opportunities (e.g., Kellogg & Raulerson, 2007; Stellmack et al, 2015). Out of all courses sampled, the 300-level experimental psychology class incorporated the most writing instruction, feedback, and opportunities for revision on literature review type assignments, although this would have primarily occurred after the assessment was completed in this course.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, having a detailed rubric with multiple criteria resulted in the discovery that students were not improving in all areas of writing equally; spelling and grammar improved the least, whereas organization and reasoning improved the most. Most previous studies of college writing improvement have only reported overall scores (Oppenheimer et al, 2017; Roohr et al, 2017; Stellmack et al, 2012, 2015). Our study adds to the work of Greenberg (2015), Haswell (2000) and Kelly-Riley (2015), all of whom used multidimensional measures of writing, though the assessed dimensions varied because our rubric was designed to be assignment- and discipline-specific.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations